2022
DOI: 10.3390/su142215004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Changes in Abundance of Culturable Microbial Community and Respiration Activities in Response to Mineral–Organic Mixture Application in Contaminated Soil

Abstract: The availability and affordability of fertilizers are the main risks currently faced by the fertilizer market. Therefore, there is a need to look for other sources of nutrient supply for plants, while taking care of soil properties. The application of fertilizers with the addition of functionalized materials could help in the efficient use of nutrients. The aim of the study was to assess the impact of the application of mixtures with the addition of zeolite–vermiculite composites (NaX–Ver) on the culturable mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The DhA in soils are usually the most sensitive indicator of environmental changes, and their activities are always affected by soil conditions through shifting the synthesis and structure of local microorganisms 39 . It was also evidenced that zeolites, due to their high porosity and well-developed specific surface area, can improve the soil’s microbial activity 26 , 27 , 40 . The DhA in amended soils was lower compared to the control, except for C9L6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DhA in soils are usually the most sensitive indicator of environmental changes, and their activities are always affected by soil conditions through shifting the synthesis and structure of local microorganisms 39 . It was also evidenced that zeolites, due to their high porosity and well-developed specific surface area, can improve the soil’s microbial activity 26 , 27 , 40 . The DhA in amended soils was lower compared to the control, except for C9L6.…”
Section: Discussionmentioning
confidence: 99%
“…It was also proved that zeolite (natural and synthetic) as an additive to fertiliser can improve the physical, chemical, and biological properties of soil 21 – 24 . Previous studies have shown that adding exogenous organic matter mixed with zeolite-carbon composite (NaX-C) and zeolite-vermiculite composite (NaX-Ver) can stimulate soil microbial activity 25 – 27 and also have a positive effect on root morphological parameters 28 . However, information about the application of these additives to the soil contaminated with PAHs is limited.…”
Section: Introductionmentioning
confidence: 99%